To Warn or Not to Warn: Management Disclosures in the Face of an Earnings Surprise. - Kasznik, Ron; Lev, Baruch (The Accounting Review, 1995)
Examines management's discretionary disclosures prior to earnings surprise. Means of informing the investors; Investors' reactions to warnings.